SAT0476 JUVENILE IDIOPATHIC ARTHRITIS IN SINGAPORE: A 10-YEAR CLINICAL EXPERIENCE. (June 2019) - Pauline Chan Ng, Poh Lin; Ooi, Pei Ling; Ang, Elizabeth; Lim, Lee Kean; Hoh, Sook Fun; Das, Lena; Book, Yun Xin; Arkachaisri, Thaschawee
Abstract : Background: Juvenile Idiopathic Arthritis (JIA) is the commonest inflammatory arthritis of childhood worldwide. Objectives: To describe the incidence, clinical characteristics and experience with JIA in Singapore over a 10-year period. Methods: A prospective study was conducted in KK Women's & Children's Hospital and National University Hospital, Singapore from Jan 2009-Dec 2018. JIA was defined and classified according to ILAR criteria 1 . Demographics and clinical information were collected for every patient diagnosed with JIA. Results: 379 children were diagnosed with JIA (60.2% male, 71.2% Chinese). Average estimated incidence was 5.8 per 100000/yr. Clinical characteristics and treatment used are summarized in Table 1 . Table 1 . *Median (IQR). Rest expressed in n (%). Disease modifying anti-rheumatic drugs (DMARD) were used in 67.8%, and younger age of diagnosis (p=0.002), longer lag time (p=0.004), males (p=0.018) and ERA (p=0.043) predicted their use. 38.3% required biologics, and males (p=0.047), longer lag time (p=0.037) and HLA-B27 positivity (p=0.030) were associated with their use. Uveitis incidence was 2.9%; 54.5% had oligoarthritis, 36.4% ERA, 9.1% polyarthritis (RF-). Younger age at JIA diagnosis was associated with uveitis (p=0.030). Conclusion: ERA is the commonest subtype of JIA in our cohort, explaining the male predominance and higher HLA-B27 positivity as compared to the West 2 . Longer lag time was associated with DMARD and biologic use, likely due to more severe disease at presentation. HLA-B27 association with biologic use may predict ineffectiveness of DMARD. Uveitis incidence was low as compared to Western literature that cites a prevalence of 11-30% 3, 4 . Young age at diagnosis is a risk factor for uveitis. Interestingly, ANA-positivity and female gender were not associated with uveitis cases. References: [1] Petty RE, et al. International League of Associations for Rheumatology classification of juvenile idiopathic arthritis: second revision, Edmonton, 2001. J Rheumatol. 2004Feb;31(2):390-2. [2] Żuber Z, et al. Prevalence of HLA-B27 antigen in patients with juvenile idiopathic arthritis. Reumatologia. 2015;53(3):125-30. [3] Angeles-Han ST, et al. Characteristics of a cohort of children with Juvenile Idiopathic Arthritis and JIA-associated Uveitis. Pediatr Rheumatol Online J. 2015;13(1):19. [4] Clarke SL, et al. Juvenile idiopathic arthritis-associated uveitis. Pediatr Rheumatol Online J. 2016;14:27. Disclosure of Interests: Poh Lin Pauline Chan Ng: None declared, Pei Ling Ooi: None declared, Elizabeth Ang: None declared, Lee Kean Lim: None declared, Sook Fun Hoh: None declared, Lena Das: None declared, Yun Xin Book: None declared, Thaschawee Arkachaisri Speakers bureau: Abbvie Pte, Ltd